a Design of an IoT-Based Control and Monitoring System for a Biogas Power Generation Plant Using POME Waste from Palm Oil Mills: a Design of an IoT-Based Control and Monitoring System for a Biogas Power Generation Plant Using POME Waste from Palm Oil Mills - Asminar Asminar; Rifki Rifki; Akhyar Muchtar; Abdul Djohar; Agustinus Lolok; Mustarum Musaruddin; Hasmina Tari Mokui; Adhi Setiawan Samsul (Journal of Renewable Energy and Smart Device, 2026)
Palm Oil Mill Effluent (POME) contains a high organic load that can be converted into biogas through anaerobic digestion and subsequently utilized for electricity generation. However, maintaining stable digester conditions requires an integrated monitoring and control system capable of observing critical operating parameters. This study presents a conceptual design and theoretical assessment of an Internet of Things (IoT)-based monitoring and control system for a POME-based biogas power plant. The proposed architecture integrates an anaerobic digester, gas holder, biogas generator, ESP32 microcontroller, temperature, pressure, methane concentration, and gas flow meter, cloud communication through MQTT/HTTP protocols, and web- and mobile-based dashboards. A threshold-based control strategy is proposed to regulate gas pressure and digester temperature. This study did not include physical system implementation or experimental field testing. Based on the adopted design assumptions, processing 300 metric tons of fresh fruit bunches generates approximately 240 m³ of POME and 6,000 m³ of biogas. Using a methane fraction of 60%, a methane calorific value of 35.7 MJ/m³, and a fixed generator efficiency of 35%, the theoretical electrical energy output is estimated at 12,495 kWh per production cycle. The proposed design provides an integrative framework for future prototype development and experimental validation of IoT-based monitoring and control in POME biogas power plants.